NETs - as predictors and targets of supportive therapy for cancer treatment - Morawiec, Maria-Laura; Kubina, Robert; Jabłońska, Ewa; Ratajczak-Wrona, Wioletta; Stępień, Sebastian; Gołębski, Maciej; Mielczarek-Palacz, Aleksandra (Frontiers in Immunology, 2025)
NETs are network-like structures consisting mainly of DNA and various proteins released by neutrophils physiologically in response to pathogens. Moreover, according to recent reports, NETs also play an important role in carcinogenesis. They are involved in all stages of carcinogenesis, assist in the process of metastasis, and their presence has been linked to higher mortality and poorer prognosis in numerous cancer types. This review focuses on anti-cancer treatments related to disintegration of existing NETs, inhibition of their formation and regulation of their formation. Cases in which the presence of NETs was associated with anti-cancer activity and the association of NETs with complications co-occurring with cancer or related to cancer treatment was presented. This paper also presents mechanisms of NETs inhibition, predicting the efficacy or resistance of anti-cancer therapy associated with NETs.